Ground Penetrating Radar Technique for Bridge Deck Inspection - Hamzeh, Layane (2013)
A Master of Science thesis in Civil Engineering by Layane Hamzeh entitled, "Ground Penetrating Radar Technique for Bridge Deck Inspection," submitted in July 2013. Thesis advisor is Dr. Sherif Yehia and Co-advisor Dr. Nasser Qaddoumi. Available are both soft and hard copies of the thesis.